Acyl-CoA synthase ACSL4: an essential target in ferroptosis and fatty acid metabolism - Ding, Kaiyue; Liu, Chongbin; Li, Li; Yang, Ming; Jiang, Na; Luo, Shilu; Sun, Lin (Chinese medical journal, 2023)
Long-chain acyl-coenzyme A (CoA) synthase 4 (ACSL4) is an enzyme that esterifies CoA into specific polyunsaturated fatty acids, such as arachidonic acid and adrenic acid. Based on accumulated evidence, the ACSL4-catalyzed biosynthesis of arachidonoyl-CoA contributes to the execution of ferroptosis by triggering phospholipid peroxidation. Ferroptosis is a type of programmed cell death caused by iron-dependent peroxidation of lipids; ACSL4 and glutathione peroxidase 4 positively and negatively regulate ferroptosis, respectively. In addition, ACSL4 is an essential regulator of fatty acid (FA) metabolism. ACSL4 remodels the phospholipid composition of cell membranes, regulates steroidogenesis, and balances eicosanoid biosynthesis. In addition, ACSL4-mediated metabolic reprogramming and antitumor immunity have attracted much attention in cancer biology. Because it facilitates the cross-talk between ferroptosis and FA metabolism, ACSL4 is also a research hotspot in metabolic diseases and ischemia/reperfusion injuries. In this review, we focus on the structure, biological function, and unique role of ASCL4 in various human diseases. Finally, we propose that ACSL4 might be a potential therapeutic target.